Peran Metode Cooperative Learning dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Siswa Kelas X di MAN 2 Kabupaten Bogor - Iklimah, Siti; Nurul, Sri; Hamdani, Ikhwan (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Based on the author's observations of class X MAN 2 Bogor Regency students, 70% of students still experience low Al-Qur'an memorization skills. With this data, it is necessary to improve learning about memorization. The purpose of this study was to find out whether there was a significant difference in improving the ability to memorize the Qur'an after the Cooperative Learning method was applied. The method that will be used in this study is the Quasi Experimental Test method. The form of this research design is Nonequivalent Control Group Design, namely research to find the effect of the Cooperative Learning method on the memorization ability of class X students at MAN 2 Bogor Regency. In this study the test was administered twice: first, students were given a pre-test to find out the amount of student memorization in both the control and experimental groups. Second, students are given a final test (post-test) using traditional methods in the control class and using the Cooperative Learning method in the experimental class. From the results of the test, it can be concluded that there was an increase in the ability to memorize the Al-Qur'an for class X MAN 2 Bogor Regency students who were taught by traditional methods. It was seen that the average number of memorization increased by 13.45 verses, and there was an increase in the ability to memorize the Al-Qur'an class X MAN 2 Bogor Regency who were taught by Cooperative Learning method seen from the average number of memorization increased by 17.95. Whereas in the T-test, there is a difference in the ability to memorize the Koran for class X MAN 2 students in Bogor Regency after the Cooperative Learning method is applied, it is seen that the significance is 0.000 <0.05, so it can be concluded that the Cooperative Learning method can increase the memorization of class X MAN 2 students Bogor Regency.